Preparing and Storing an Emergency Safe Drinking Water Supply - Shuchi Shukla; Thomas Obreza (EDIS)
The purpose of this fact sheet is to emphasize the importance of having a personal safe drinking water supply during an emergency, and to describe the steps that Florida's citizens should take to prepare and store drinking water. This document is SL220, a fact sheet of the Soil and Water Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: October 2004.